PENGARUH MEDIA MASSA DALAM KEBIJAKAN PENDIDIKAN - Toha Makhshun; Khalilurrahman Khalilurrahman (Universitas Islam Sultan Agung, 2018)
The role of the mass media is very decisive in the delivery of information and a government policy. In line with the increasing level of communication technology development, the communication method rapid development as well. But all of that has the same accentuation that communicators convey messages and ideas to the publik. When detailed more concretely, the method of communication in the contemporary world which is the development of verbal and nonverbal communication covers many fields, including journalism, publik relations, advertising, exhibitions/ expositions, and publikations that will influence political culture. This paper will discuss more about the influence of mass media in education policy.